A Survey of the Algorithms Used for Traffic Light Scheduling Systems - Farooq, Asif; Iqbal, Tahir; Haq, Ehtashamul; Ghaffar, Abdul (UMT Artificial Intelligence Review, 2022)
Traffic congestion are among the most important issue that a country needs to confront due to increasing volume of vehicles around the world, particularly in the large urban areas. As a result, the requirement begins for modeling and improving traffic management procedures to improve the growing need. In order to address traffic problems in urban areas a smart traffic management method is the need of time. The solution in this paper is found through the dimensions of traffic mass on the roads. The core objective of this paper is to highlight latest techniques algorithm which has been used for scheduling traffic lights and a comparison based on achieved accuracy.